Concentration measurement of injected gaseous fuel using quantitative schlieren and optical tomography - Iffa, Emishaw D. (2010)
In this paper, the quantitative schlieren method is extended to measure the concentration field of an injected gaseous fuel along several planes perpendicular to the jet axis. Background Oriented Schlieren (BOS) is used as a quantitative flow field concentration measurement based on the deflection made by features in the background pattern. The flow field which is located between the camera and the background pattern changes the intensity value of the background points in the transfer medium. The optical flow algorithm, which is used to measure the deflection vectors in the background due to the change in index of refraction, is modified to consider the change in intensity of the background image due to the flow field. Optical tomography is used as a tool to extract the index of refraction of the gaseous field. Mole fraction values at different planes perpendicular to the jet axis are obtained and displayed.